“Em teu meio não haverá nenhum pobre” (Dt 15,4) a intertextualidade do shemá nas comunidades essenia de Qumran e cristã segundo At 4,32 - Borgonovi, Emerson Pedroso (2025)
This research arises from the hypothesis that the manifestation of the first Christian communities described in the Acts of the Apostles and, their peculiar way of being and living, did not occur in an exclusively innovative and unusual way, but would be the result of influences, “appropriations” and/ or “adaptations”. Luke, to describe them, accesses the Deuteronomic memorial of the people of Israel synthesized and idealized in the shema: a single fraternal people who heard YHWH and, therefore, believe and love Him with all their heart, soul and strength (cf. Dt 6, 4-5). Furthermore, it will receive cultural, religious and socioeconomic influences from the groups formed and present in Second Temple Judaism. Among these influences, the socioeconomic experience of the Essene community of Qumran stands out, in which the community sharing of goods is highlighted, this being the first group to put it into practice as a form of fraternity among its members. Luke indicates his desire to convey that the Church in its genesis, formed by Jews and later by pagans, has its roots in the socio-religious experience of the chosen people